Risk Stratification Using Neoadjuvant Rectal Score in the Era of Neoadjuvant Chemoradiotherapy: Validation With Long-term Outcome Data. Issue 1 (January 2021) - Lim, Yu Jin; Song, Changhoon; Jeon, Seung Hyuck; Kim, Kyubo; Chie, Eui Kyu
Abstract : BACKGROUND: Despite the widespread use of neoadjuvant chemoradiotherapy, there is no prognostic surrogate marker established in locally advanced rectal cancer. OBJECTIVE: This study evaluated the role of neoadjuvant rectal score as a prognostic factor to stratify individual-level risks of survival and tumor recurrence. DESIGN: This is a retrospective study. SETTINGS: This study was conducted at the Seoul National University Hospital. PATIENTS: A total of 397 patients who underwent chemoradiotherapy plus total mesorectal excision were analyzed. INTERVENTIONS: There was no intervention. MAIN OUTCOME MEASURES: Harrell C statistic and receiver operating characteristic analysis, as well as Cox regression analysis, were used to assess the prognostic strength. RESULTS: The low (<8), intermediate (8–16), and high (>16) neoadjuvant rectal score groups included 91 (23%), 208 (52%), and 98 patients (25%). A high neoadjuvant rectal score was independently associated with inferior overall survival and disease-free survival ( p = 0.011 and 0.008). Regarding the prognostic models adjusted for neoadjuvant rectal score (I) and ypT/N stage (II), the c-index was higher in model I (0.799 and 0.787, p = 0.009 for overall survival; 0.752 and 0.743, p = 0.093 for disease-free survival). The predictive ability of the neoadjuvant rectal score was superior to tumor regression grade, ypT, and ypN in the receiver operating characteristic analyses ( p < 0.05 for all). Adjuvant chemotherapy was associated with better overall and disease-free survival ( p = 0.003 and 0.052) in the high neoadjuvant rectal score group. LIMITATIONS: Potential selection bias attributed to the retrospective study design was a limitation. CONCLUSIONS: We verified the applicability of the neoadjuvant rectal score to stratify the relapse risk at the individual level for patients with stage II/III rectal cancer undergoing neoadjuvant chemoradiotherapy. Additional studies are needed to validate the usability of neoadjuvant rectal score levels as a determinant of adjuvant strategy. See Video Abstract at http://links.lww.com/DCR/B354 . ESTRATIFICACIÓN DE RIESGO UTILIZANDO LA PUNTUACIÓN RECTAL NEOADYUVANTE EN LA ERA DE LA QUIMIORRADIOTERAPIA NEOADYUVANTE: VALIDACIÓN CON DATOS DE RESULTADOS A LARGO PLAZO: ANTECEDENTES: A pesar del uso generalizado de la quimiorradioterapia neoadyuvante, no existe un marcador subrogado pronóstico establecido en el cáncer de recto localmente avanzado. OBJETIVO: Este estudio evaluó el papel de la puntuación rectal neoadyuvante como factor pronóstico para estratificar los riesgos a nivel individual de supervivencia y recurrencia tumoral. DISEÑO: Este es un estudio retrospectivo. ESCENARIO: Este estudio se realizó en el Hospital de la Universidad Nacional de Seúl. PACIENTES: Se analizaron un total de 397 pacientes que se sometieron a quimiorradioterapia más escisión mesorrectal total. INTERVENCIONES: No hubo intervención. PRINCIPALES MEDIDAS DE RESULTADO: El análisis estadístico C de Harrell y las características operativas del receptor, así como el análisis de regresión de Cox, se utilizaron para evaluar la fuerza pronóstica. RESULTADOS: Los grupos de puntaje rectal neoadyuvante bajo (<8), intermedio (8–16) y alto (> 16) incluyeron 91 (23%), 208 (52%) y 98 (25%) pacientes, respectivamente. Una puntuación rectal neoadyuvante alta se asoció independientemente con una supervivencia general y una supervivencia libre de enfermedad inferiores ( p = 0.011 y 0.008, respectivamente). Con respecto a los modelos pronósticos ajustados por la puntuación rectal neoadyuvante (I) y el estadio ypT/N (II), el índice c fue mayor en el modelo I (0.799 y 0.787, p = 0.009 para la supervivencia general; 0.752 y 0.743, p = 0.093 para supervivencia libre de enfermedad). La capacidad predictiva de la puntuación rectal neoadyuvante fue superior al grado de regresión tumoral, ypT y ypN en los análisis de características operativas del receptor ( p <0.05 para todos). La quimioterapia adyuvante se asoció con una mejor supervivencia global y libre de enfermedad ( p = 0.003 y 0.052, respectivamente) en el grupo de puntaje rectal neoadyuvante alto. LIMITACIONES: El sesgo de selección potencial debido al diseño retrospectivo del estudio fue la limitación. CONCLUSIONES: Verificamos la aplicabilidad de la puntuación rectal neoadyuvante para estratificar el riesgo de recurrencia a nivel individual para pacientes con cáncer rectal en estadio II/III sometidos a quimiorradioterapia neoadyuvante. Se necesitan más estudios para validar la usabilidad de los niveles de puntuación rectal neoadyuvante como determinante de la estrategia adyuvante. Consulte Video Resumen en http://links.lww.com/DCR/B354 . Abstract : Supplemental Digital Content is available in the text.